ESOPHAGEAL CARCINOMA AND THE RESULTS OF PALLIATIVE ESOPHAGEAL INTUBATION - Hanefi ÇAVUŞOĞLU; Ahmet MUSOĞLU; Nadir YÖNETÇİ and Ulus AKARCA and Ahmet AYDIN and Ömer ÖZÜTEMİZ (Turkish Journal of Gastroenterology, 2020)
-